Smart solar louvre shading system for residential building in Malaysia / Adib Luqman Daing Ismail and Asmat Ismail - Daing Ismail, Adib Luqman; Ismail, Asmat (2024)
Solar louvre shading or awning prevents solar radiation from entering the building. However, dirt and debris on the solar panel can affect solar louvre shading performance. Many studies have shown that the current louvre shading requires regular maintenance to clean the panels. Furthermore, the overheating problem could also affect the technology's sustainability and reduce the performance of solar panels. Therefore, this project aims to improve solar shading technologies by innovating the smart solar louvre shading system. Three research objectives have been developed to achieve this aim, i.e., identify the common problem with the existing solar shading devices, propose a smart solar louvre shading system for residential buildings in Malaysia, and suggest the marketability potential of smart solar louvre shading system. This study adopts several research methodologies, such as reviewing literature, idea creation and 3D simulation modelling using SketchUp and Lumion software. Key findings of this study reveal that present solar louvre shading systems have issues such as high startup costs and debris buildup that makes maintenance difficult. Self-cleaning mechanisms and rain sensors in the intelligent solar louvre shading system improve efficiency and reduce maintenance costs. This study found that sophisticated solar louvre shading systems can optimise lighting, cleaning mechanisms, and maintenance to reduce building energy usage, as well as improve the outdoor atmosphere, supporting modern home construction's sustainability goals.